Sustainability and Authenticity of Chinese Traditional Crafts in the Contexts of Luxury and Tourism - Meng, Kelly; Hitchcock, Michael (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
Chinese crafts have been examined from economic, historical and aesthetic perspectives, but rather less attention has been devoted to them in the literature on luxury and tourism. When considering the former, it is worth noting that some of the world’s leading brands had their origins in craft businesses, notably Louis Vuitton, and that craft skills remain important for this industry in the 21st century. On the other hand, there is a common assumption that craft souvenirs represent a cheap and debased version of human material culture but, as many academics have asserted souvenirs come in a wide variety of forms, including what Graburn (2000) has called ‘pride goods’, in which peoples visited by tourists sell products that are simultaneously economically useful and boosters of esteem on behalf of the producing community. It is with these thoughts in mind that we turn our attention to the production of Chinese craft products in the early 21st century. As one of the leading handicraft producers in the world, the expanding demand for Chinese craft products has generated commercial opportunities and strong economic returns, it has also created challenges to the Chinese traditional crafts sector which may influence the direction and sustainability of its future development, and as such is worthy of deeper investigation and discussion. Keywords: Chinese traditional crafts, luxury, tourism, sustainability, authenticity